NEW RESULT ON A FLUID FLOW INDUCED BY A ROTATING MAGNETIC FIELD (FULafia Journal of Science and Technology, 2018)
This research paper provides a new result on induced fluid flow in a circular cylinder under the influence of a rotating magnetic field. Maxwell’s induction equation and asymptotic technique are used to obtain the new result and it is observed that the convective term which Mofatt neglected in his work is significant in the boundary layer.
Keywords: Induced fluid flow; Maxwell’s Induction equation; Rotating Magnetic field; Convective term; Boundary layer